2022
DOI: 10.3390/medsci10020030
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Venous Thromboembolism in Critically Ill Patients with SARS-CoV-2 Infection Compared with Critically Ill Influenza and Community-Acquired Pneumonia Patients: A Retrospective Chart Review

Abstract: The rate of venous thromboembolism in COVID-19 patients has been reported to be 30% (deep vein thrombosis 20% and pulmonary embolism 18%). This has been shown to be higher in COVID-19 patients admitted to the ICU. Prophylactic anticoagulation may be sufficient at ward level, but not in intensive care. A retrospective chart review was undertaken in a large university hospital. The review included 276 patients from COVID-19 Wave 1, COVID-19 Wave 2, influenza, and community-acquired pneumonia groups. The timefram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
2
1
0
Order By: Relevance
“…Studies have confirmed that infection with SARS-CoV-2 can induce a massive thrombotic state [41][42][43]. We have also observed this phenomenon, and clinicians at our dialysis center found that even when receiving anticoagulant doses (1000-3000IU) of low molecular weight heparin, some patients still found that intravenous pot dialyzer tubing developed during dialysis.…”
Section: Laboratory Indicatorssupporting
confidence: 68%
“…Studies have confirmed that infection with SARS-CoV-2 can induce a massive thrombotic state [41][42][43]. We have also observed this phenomenon, and clinicians at our dialysis center found that even when receiving anticoagulant doses (1000-3000IU) of low molecular weight heparin, some patients still found that intravenous pot dialyzer tubing developed during dialysis.…”
Section: Laboratory Indicatorssupporting
confidence: 68%
“…Studies have con rmed that infection with SARS-CoV-2 can induce a massive thrombotic state [41][42][43]. We have also observed this phenomenon, and clinicians at our dialysis center found that even when receiving anticoagulant doses (1000-3000IU) of low molecular weight heparin, some patients still found that intravenous pot dialyzer tubing developed during dialysis.…”
Section: Laboratory Indicatorssupporting
confidence: 54%
“…It is also important emphasizing that there are some pathophysiological explanations indicating that patients who develop AF de novo during pneumonia have increased risk of bleeding events (depletion of coagulation factors and platelets as a result of inflammatory response during infection) ( 53 ). Based on the available data, it can be conservatively assumed that among patients with SARS-CoV2 infection, the risk of both thromboembolic and hemorrhagic complications to which AF patients are particularly vulnerable is at least comparable to that of patients with pulmonary infection caused by other pathogens (bacterial or viral) ( 51 , 53 , 54 ). Considering the rationale presented above, it is worth emphasizing that the association between AF and pneumonia is not limited only to the COVID-19 pandemic, and the results we obtained may provide a point of consideration for patients with community acquired pneumonia caused by other causes than SARS-CoV2 virus infection.…”
Section: Discussionmentioning
confidence: 99%